Phase relationships, electrical transport properties and redox behavior of oxides in the PrVO4-Ca2V2O7 system for SOFC applications - Pinto, Rui (2022)
Rare-earth and alkaline-earth vanadates attract attention as prospective materials for electrochemical applications, in particular, as redox-reversible components for fuel electrodes of solid oxide fuel cells (SOFC). An essential advantage of (Ln,A)VOx-derived components of SOFC anodes is their anticipated resistance to carbon deposition and sulfur-containing impurities, which is critical for hydrocarbon- and biogas-fueled SOFCs. The present work was focused on the oxides of the PrVO4-Ca2V2O7 system as fuel electrode precursors, with an emphasis on phase formation, redox and thermomechanical behavior, and electrical properties. PrVO4, Ca2V2O7 and the ceramics with the nominal composition Pr1-xCaxVO4-d (x = 0.02-0.20) were prepared by the conventional solid-state route. Ceramics samples were sintered at 1000°C for Ca2V2O7 and 1300°C for other materials. XRD demonstrated the formation of phase-pure Pr1-xCaxVO4-d solid solutions with the tetragonal zircon-type structure for up to 5 at.% of calcium in Pr sublattice. At the same time, SEM/EDS suggest a lower solubility indicated by the presence of Ca-V-O phase impurities. Doping by calcium increases mixed ionic-electronic conductivity of Pr(Ca)VO4 ceramics under oxidizing conditions. The electronic contribution is p-type and decreases with reducing p(O2). The reduction of Pr1-xCaxVO4-d ceramics in a 10%H2-N2 atmosphere at 800°C leads to phase separation and formation of perovskite-like PrVO3 and CaVO3 phases. The redox behavior of PrVO4-Ca2V2O7 ceramics on isothermal cycling between air and 10%H2-N2 was studied by impedance spectroscopy, thermogravimetry, dilatometry and post-mortem XRD analysis.